Calreticulin is the dominant pro-phagocytic signal on multiple human cancers and is counterbalanced by CD47 - Chao, Mark P; Jaiswal, Siddhartha; Weissman-Tsukamoto, Rachel; Alizadeh, Ash A; Gentles, Andrew J; Volkmer, Jens; Weiskopf, Kipp; Willingham, Stephen B; Raveh, Tal; Park, Christopher Y; Majeti, Ravindra; Weissman, Irving L (Science translational medicine, 2010)
Under normal physiological conditions, cellular homeostasis is partly regulated by a balance of pro- and anti-phagocytic signals. CD47, which prevents cancer cell phagocytosis by the innate immune system, is highly expressed on several human cancers including acute myeloid leukemia, non-Hodgkin's lymphoma, and bladder cancer. Blocking CD47 with a monoclonal antibody results in phagocytosis of cancer cells and leads to in vivo tumor elimination, yet normal cells remain mostly unaffected. Thus, we postulated that cancer cells must also display a potent pro-phagocytic signal. Here, we identified calreticulin as a pro-phagocytic signal that was highly expressed on the surface of several human cancers, but was minimally expressed on most normal cells. Increased CD47 expression correlated with high amounts of calreticulin on cancer cells and was necessary for protection from calreticulin-mediated phagocytosis. Blocking the interaction of target cell calreticulin with its receptor, low-density lipoprotein receptor-related protein, on phagocytic cells prevented anti-CD47 antibody-mediated phagocytosis. Furthermore, increased calreticulin expression was an adverse prognostic factor in diverse tumors including neuroblastoma, bladder cancer, and non-Hodgkin's lymphoma. These findings identify calreticulin as the dominant pro-phagocytic signal on several human cancers, provide an explanation for the selective targeting of tumor cells by anti-CD47 antibody, and highlight the balance between pro- and anti-phagocytic signals in the immune evasion of cancer.